A Voices-Centered Approach to Transitional Justice: Youth-led Activism and Artistic Initiatives Open Spaces for Broad Community Engagement. (30th April 2022) - Jmal, Nadia; Ladisch, Virginie
ABSTRACT: In response to a global movement demanding justice for historically oppressed communities, there are increased calls for transitional justice approaches to help unravel legacies of colonization, slavery and marginalization. Applying transitional justice approaches to contexts of structural injustice raises new questions that push the boundaries of the field. In the face of these challenges, this article explores ways to conceptualize transitional justice as a dynamic, ongoing relational process that centers victims and involves bystanders, beneficiaries and the general public in meaningful and appropriate ways. Across different socio-political contexts, we look to new voices, in particular youth voices and creative approaches, for inspiration on how to bring more people into the conversation to address emerging dilemmas in consolidated democracies. Much can be learned from the dynamic spaces created by young people to encourage a more transformational process of reckoning with past legacies to advance a more just future.